The Genesis and Growth: A Historic Exploration of the People’s Democratic Party (PDP) in Jammu and Kashmir (International Journal of Scientific Research in Science and Technology, 2024)
This study delves into the historic evolution of the People’s Democratic Party (PDP), a significant political entity in the union territory of Jammu and Kashmir. Founded in 1999 by Mufti Mohammad Sayeed, the PDP emerged as a key player in the region’s political landscape, offering an alternative to the established National Conference. The exploration begins by tracing the origins of the PDP, focusing on the socio-political context that led to its formation, including the demand for a party that could address the unique aspirations and grievances of the people of Jammu and Kashmir. The study further examines the PDP’s early years, highlighting the strategies employed by its founders to gain traction among the electorate. This includes an analysis of the "healing touch" policy, which became synonymous with the party’s approach to governance and conflict resolution. The PDP’s commitment to advocating for greater autonomy and its efforts to engage in dialogue with separatists and neighbouring Pakistan are also scrutinized to understand how these policies shaped the party’s identity and electoral success. As the study progresses, it explores the pivotal moments in the PDP’s journey, such as its coalition governments with both the Congress and the Bharatiya Janata Party (BJP). These alliances are critically analyzed to understand their impact on the party’s core values, internal dynamics, and public perception. The controversial coalition with the BJP, in particular, is explored in depth, shedding light on the ideological compromises and the subsequent fallout within the party and among its supporters. The latter part of the study addresses the challenges faced by the PDP, especially in the wake of the abrogation of Article 370 in August 2019, which stripped Jammu and Kashmir of its special status. The political ramifications of this move, including the detention of party leaders and the subsequent decline in the PDP’s influence, are discussed in detail. The study concludes by reflecting on the PDP’s legacy and its potential future in the ever-evolving political environment of Jammu and Kashmir. Through a comprehensive examination of its genesis and growth, this study provides a nuanced understanding of the PDP’s role in shaping the political narrative of Jammu and Kashmir. It offers valuable insights into the complexities of regional politics and the challenges of balancing regional aspirations with national integration in one of India’s most contentious territories.